Board Gender Diversity Toward Corporate Social Responsibility Disclosure in Palestinian Companies:Financial Performance as Mediation - Omar Tarda; Dato' Hasnah Hj Haron; Nathasa Mazna Ramli; Supiah Salleh (Taylor & Francis, 2025)
Indexed by Scopus